The administration of the central prisons Sabah / Uzair Yahaya - Uzair, Yahaya (1977)
To most people prison is nothing but an institution where individuals, who had previously broken the law, are kept. Such conception reigns supreme particularly in the state of Sabah where majority of its population are still illiterate, if not, very poorly educated. Even the educated ones have an indifferent attitude towards the prison institution. This is by reason of the fact that prisons has nothing much to offer that can attract public attention. Consequently it remains an institution where very few know anything about. Little do they know regarding the aims and objectives of the prison institution. It is common knowledge awong many and it is a misconception that the purpose of prisons is to punish. Therefore the public should not have anything to do with those to be punished. Such notion needs to be changed and maybe it can be said that one of the objects of this paper is to change the public attitude towards the institution. The Sabah prisons has undergone tremendous progress. Prior 1952 a well organised prison institution has no existence at all. During those days prisoners had to live in Police Lockups. Maybe it can be said that during those days the actual aim and policy of a lockup or a prison is to punish. After all the Sabah was a colony and the writer firmly believes that it was never the object of the colonialists to assist the locals or natives.